Sticks and Carrots: The Effect of Contract Frame on Effort in Incomplete Contracts - Christ, Margaret H.; Sedatole, Karen L.; Towry, Kristy L. (The Accounting Review, 2012)
ABSTRACT In this study, we examine the effect of incentive contract framing on agent effort in an incomplete contract setting. Prior research suggests that when governed by complete incentive contracts, agents exert greater effort under penalty contracts relative to bonus contracts. However, in an incomplete contract setting, in which the incentive contract does not govern all tasks for which the agent is responsible, the agent's trust in the principal is relevant. In this setting, we predict that bonus contracts create a more trusting environment, and this effect spills over to tasks not governed by the incentive contract, such that bonus contracts elicit greater effort on these tasks as compared to penalty contracts. We develop and experimentally validate a theoretical model of the effects of contract frame on trust and effort in this incomplete contract setting. The main intuition behind the model is that the framing of an incentive contract affects the degree to which the contract terms are interpreted by the agent as a signal of mistrust. More specifically, penalty contracts engender greater distrust than do bonus contracts and, therefore, when contracts are incomplete, penalty contracts lead to lower effort on tasks not governed by the contract than do bonus contracts.